The Effect of The Teams Games Tournament (TGT) Learning Model on Students' Learning Results in Mathematics Subjects For Class III Primary School Students - Aprimadedi, Aprimadedi; Marlianda, Rendi; Verliana, Verliana (The Future of Education Journal, 2024)
This research is motivated by the learning process that has not shown interesting progress and has yet to encourage active participation from students. This situation directly negatively impacts students' academic performance in mathematics, which remains relatively low. Therefore, there is a need for efforts to develop more effective and engaging learning methods to improve students' learning outcomes in this subject. This study aims to obtain information on the extent of the influence of the Teams Games Tournament (TGT) learning model on the mathematics learning outcomes of third-grade elementary school students. This research is an experimental study using a quasi-experimental design, specifically a Posttest Only Control Design. The research was conducted at SDN 20 Sitiung, Sitiung District, Dharmasraya Regency. The sample consisted of 49 students, representing all students in grade III. The data collection instrument used was a 20-item multiple-choice test that has been tested for validity and reliability. The results showed that the average posttest score for the experimental class was 73.54, while the control class had an average posttest score of 44. Data analysis of the posttest results, using an Independent Sample Test, indicated a significance value of 0.000 < 0.05. Based on the criteria, if the significance is < 0.05, then H0 is rejected and Ha is accepted. Thus, it can be concluded that there is a significant effect of the application of the Teams Games Tournament (TGT) learning model on the mathematics learning outcomes of third-grade students at SDN 20 Sitiung